A Taxonomy and Survey of Energy Efficient Resource Allocation Schemes for Cloud Datacenter - Satveer,; Singh, Mahendra (International Journal of Computer Sciences and Engineering, 2025)
The cloud computing is gaining the popularity rapidly due to its esteem services benefits and high computational demand of social, business, web and scientific applications. The cloud datacenters across the world are consuming high volume of energy thus affecting the environment also. The resource allocation in cloud is a key factor to achieve energy efficiency. In this paper, we reviewed the energy concept and different kinds of resource allocation schemes being used in cloud datacenters and went on to derive a taxonomical classification of these strategies based upon various metrics.